Prevalence, characterization and intervention of Escherichia coli o157 in finishing cattle - Fox, J. Trent (Kansas State University, 2007)
Escherichia coli O157 is a major foodborne pathogen. The bovine gut is the primary reservoir and the organism is shed in the feces, which serves as the major source of contamination. The objectives of our research on E. coli O157 were to 1) determine prevalence and characterize presence in the rectoanal mucosa of cattle, 2) rationalize preferential prevalence in the hindgut, 3) evaluate fecal prevalence and concentration in relation to carcass contamination 4) determine the efficacy of preharvest intervention strategies to reduce fecal prevalence and/or concentration in cattle. We determined that E. coli O157 isolated from the rectoanal mucosa were similar to fecal isolates. We evaluated methods of enumeration in cattle feces to identify fecal samples with > 10[superscript3] and 10[superscript4] CFU of E. coli O157/g. We observed that prevalence of E. coli O157 on carcasses was correlated with high-shedders. We identified gluconic acid as a substrate which stimulates growth of E. coli O157 in fermentations with ruminal microbial or fecal microbial inocula from cattle. This may explain the preference to persist or colonize the hindgut because gluconic acid is a component of colonic mucin. Additionally, we evaluated the effects of cattle diets (two grain types and two grain processing methods), which present different amounts of fermentable starch to the hindgut, on prevalence of E. coli O157. Dry-rolled grain-based diets reduced prevalence of E. coli O157, possibly because of increased flow of starch to the hindgut. Competitive exclusion cultures of E. coli in in vitro fermentations reduced E. coli O157 in ruminal microbial inoculum, but in fecal microbial inoculum cultures were only efficacious when gluconic acid also was added. Lastly, we evaluated a vaccine which targeted the siderophore receptor/porin proteins of E. coli O157. The vaccine reduced prevalence, the total number of days cattle tested positive, and the total number of days cattle were identified as high-shedders of E. coli O157. In summary, our research adds further knowledge to the literature about E. coli O157 in the hindgut, provides methods to identify high-shedding animals, demonstrates the importance of high-shedding animals, and offers information about potential preharvest interventions.
Keywords: Escherichia coli O157; Beef cattle; Bovine hindgut ecology; Preharvest intervention; Carcass contamination; Agriculture, Animal Pathology (0476); Agriculture, Food Science and Technology (0359); Biology, Microbiology (0410)